Makna Simbolik Tokoh Gareng Bagi Masyarakat Milenial - Edwardus Bernard Elvis Berty; Denny Firmanto (IKIP Budi Utomo Malang, 2021)
The focus of this study is to explore the richness of symbolic meanings in Gareng figures for the Millennial community. Gareng is one of the figures from the Punakawan group. Punakawan is a group of puppet characters whose role is less visible when compared to the famous Five Pandavas. Because Gareng's role is not very visible, the philosophical meanings of Gareng are somewhat